2005
DOI: 10.1021/tx050144x
|View full text |Cite
|
Sign up to set email alerts
|

Structures and Biological Properties of DNA Adducts Derived from N-Nitroso Bile Acid Conjugates

Abstract: A kind of N-nitrosobile acid conjugate, N-nitrosotaurocholic acid (NO-TCA), was incubated with calf thymus DNA, and formation of an adduct was detected by the 32P-postlabeling method under nuclease P1 conditions. To examine the nucleotides containing the adduct from NO-TCA, each of 2'-deoxyribonucleotide 3'-monophosphates (3'-dAp, 3'-dGp, 3'-dCp, or 3'-Tp) was incubated with NO-TCA. The same adduct spot was detected in the reaction of NO-TCA with 3'-dCp. The structure of this adduct was determined to be 3-etha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 35 publications
2
20
0
Order By: Relevance
“…In addition, some previous researchers strongly suggested that the major source of nitrosable amides in the human body is the conjugated bile acids, and some bile acids might be Nnitrosated in the stomach or intestines to form potentially mitogenic compounds [7][8][9][10]. It is also suggested that DNA adducts might be derived from N-nitroso-bile acid conjugates and related to human carcinogenesis as endogenous mutagens [11]. Chemically synthesized Nnitroso-bile acids also strongly caused a mutant fraction in a human lymphoblast assay [12].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some previous researchers strongly suggested that the major source of nitrosable amides in the human body is the conjugated bile acids, and some bile acids might be Nnitrosated in the stomach or intestines to form potentially mitogenic compounds [7][8][9][10]. It is also suggested that DNA adducts might be derived from N-nitroso-bile acid conjugates and related to human carcinogenesis as endogenous mutagens [11]. Chemically synthesized Nnitroso-bile acids also strongly caused a mutant fraction in a human lymphoblast assay [12].…”
Section: Introductionmentioning
confidence: 99%
“…36 N-nitroso bile acid conjugates induced revertants on TA100, which detects base pairs change mutations, but not with TA98, a detector of frame-shift mutations. 37 With the "C" reaction mixture, the behavior was different from "A" and "B" systems: R.C. exceeded the value of 2.00 only for the TA98 strain.…”
Section: Resultsmentioning
confidence: 94%
“…Therefore, they increase in number each year. However, there is an increasing evidence that some substances which are normally present in the human or animal bodies may, under certain circumstances, exhibit genotoxic effects, therefore acting as endogenous mutagenic agents (Lutz, 1990;Totsuka et al, 2005). Probably the best studied endogenous mutagenic agents are oestrogenic hormones Schallreuter et al, 2006).…”
Section: Resultsmentioning
confidence: 99%